Patrons of history : nobility, capital and political transitions in Poland - Jakubowska, Longina (Ashgate, 2012)
Drawing on rich interview material spanning fifteen years, Patrons of History sheds light not only on communism as it existed and the stratification that persisted under such regimes, but also on the functioning of relationships of power and the ways in which privilege can be studied in the contemporary world. As such, this book will appeal to anthropologists, sociologists, ethnographers and historians interested in cultural and social capital, inequality and resistance.